Desain modifikasi dari resin-retained fixed partial denture (Modification design of resin-retained fixed partial denture) - Lilis Sukmayani; Deddy Firman (Journal of Dentomaxillofacial Science, 2014)
Modern Dentistry tends to achieve esthetic and efficiency of treatment. Patient will be interfered with edentulouscondition in longterm, especially for anterior tooth. Minimal tooth preparation and short visiting time will be chosenby most of patients. Resin-retained fixed partial denture can be the choice of treatment for partially edentulous tooth,as definitive prosthethic or interim prosthetic. An aspect for the succesfull resin-retained fixed partial denture is thedesign of bridgework. Many dentistsare avoid to provide adhesive bridge for their patients because of its high failurerates. This paper discussed about resin-retained fixed partial denture design as information for the dentists to get theright design for succes rate guarantee.